Data center handbook - Geng, Hwaiyu (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
"Organizations in need of high-speed connectivity and nonstop systems operations depend upon data centers for a range of deployment solutions. A data center is a facility used to house computer systems and associated components, such as telecommunications and storage systems. It generally includes multiple power sources, redundant data communications connections, environmental controls (e.g., air conditioning, fire suppression) and security devices." --
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Electronic data processing departments -- Design and construction -- Handbooks, manuals, etc; Electronic data processing departments -- Security measures -- Handbooks, manuals, etc; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Electronic books; Electronic books